2017
DOI: 10.1021/acs.energyfuels.7b00042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Flame Configuration and Soot Aging on Soot Nanostructure and Reactivity in n-Butanol-Doped Ethylene Diffusion Flames

Abstract: Soot has received considerable attention since it is a major pollutant in exhaust gas from fossil fuel combustion and it causes adverse climate and health effects. This work focused on soot morphology, nanostructure, and reactivity variations regarding the soot collected in different flame configurations of n-butanol-doped ethylene inverse diffusion flame (IDF) and normal diffusion flame (NDF) at different heights above burner surface (HAB = 20, 30, and 40 mm). The effects of flame configuration and soot aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 99 publications
(221 reference statements)
0
7
0
Order By: Relevance
“…In the last decades, the techniques and methods to characterize the structure of soot particles have been considerably improved . In particular, thermophoretic sampling (TS) combined with the analysis of transmission electron microscopy (TEM) images has allowed better understanding of soot morphology and evolved into a powerful tool to obtain various morphological parameters of soot particles, soot volume fraction, , and recently the local flame velocity …”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, the techniques and methods to characterize the structure of soot particles have been considerably improved . In particular, thermophoretic sampling (TS) combined with the analysis of transmission electron microscopy (TEM) images has allowed better understanding of soot morphology and evolved into a powerful tool to obtain various morphological parameters of soot particles, soot volume fraction, , and recently the local flame velocity …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, combined with the image processing algorithms proposed by Vander Wal et al in refs and , the photographed HRTEM images were further quantified to acquire characteristic parameters such as fringe length and fringe tortuosity by the homemade MATLAB code. This analysis method has been extensively applied in the research of soot formation in various flame configurations. ,,, …”
Section: Experimental Methodologiesmentioning
confidence: 99%
“…In addition, it has been found that for mature soot near the flame tip, the particles in the n-butanol flame have the largest fringe length and tortuosity, as well as the smallest layer spacing, which has the greatest degree of graphitization. Ying and Liu 117,118 studied the effects of four isomers of butanol addition to ethylene on soot nanostructures and reactivity in inverse diffusion flames (IDF) and normal diffusion flames (NDF) using high-resolution transmission electron microscopy (HRTEM), Raman spectroscopy, thermogravimetric analyzer (TGA) and elemental analyzer techniques. The results showed that the soot particles in the IDF flame with addition of butanol exhibit highly heterogeneous nanostructures, while in NDF flames, soot exhibits a typical core–shell structure.…”
Section: Butanolmentioning
confidence: 99%